2012
DOI: 10.1111/j.1440-1819.2012.02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive changes in topiramate‐treated patients with alcoholism: A 12‐week prospective study in patients recently detoxified

Abstract: Topiramate-treated patients recently detoxified from alcohol usually have an improvement of their cognitive function, especially in the language and delayed recall domains. This phenomenon may be caused by the greater influence of cognitive recovery associated with decreased drinking as compared with topiramate-induced cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Despite these test results, the TOP group did not report more subjective complaints of memory problems than the PLA group over the course of the trial. These findings are generally consistent with previously reported mixed observations on the effects of topiramate on learning and memory (Aldenkamp et al, 2000, Lee et al, 2003), but different from Likhitsathian and coworkers (Likhitsathian et al, 2012) who found no decrease in cognitive functioning in an open trial of topiramate in AUD patients. Given the limited sample size, we were unable to conduct any meaningful statistical analyses to definitively conclude that the cognitive impairment observed in this population was caused only by topiramate treatment and was unrelated to continued alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite these test results, the TOP group did not report more subjective complaints of memory problems than the PLA group over the course of the trial. These findings are generally consistent with previously reported mixed observations on the effects of topiramate on learning and memory (Aldenkamp et al, 2000, Lee et al, 2003), but different from Likhitsathian and coworkers (Likhitsathian et al, 2012) who found no decrease in cognitive functioning in an open trial of topiramate in AUD patients. Given the limited sample size, we were unable to conduct any meaningful statistical analyses to definitively conclude that the cognitive impairment observed in this population was caused only by topiramate treatment and was unrelated to continued alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, while Likhitsathian and colleagues described cognitive changes in an open trial of topiramate in AUD (Likhitsathian et al, 2012), to our knowledge, we report the first placebo-controlled study of topiramate's neurocognitive adverse effects in a trial focusing on alcohol use. Limitations of the study include its sample size, consistent with the study's pilot nature, which may have decreased power to detect significant differences between topiramate and placebo despite there being large percent differences.…”
Section: Discussionmentioning
confidence: 80%
“…These impairments are frequent in psychoactive substance users and can affect a large set of cognitive functions: problem resolution, learning, memory, etc. Previous research stated that cognitive impairments could act on care efficacy, treatment outcomes or substance use during treatment (Aharonovich, Nunes, & Hasin, 2003;Likhitsathian et al, 2012;Marceau, Lunn, Berry, Kelly, & Solowij, 2016).…”
Section: Factors Predicting Dropout Of Addiction-specialized Treatmentmentioning
confidence: 99%
“…Another 12-week, double-blind placebo-controlled study revealed that, in addition to reducing drinking and craving, topiramate improved performance in impulsivity paradigms [106]. Even though cognitive complaints are common, cognitive improvement (likely due to abstinence or decreased drinking outweighing topiramate's cognitive adverse effects) was observed at the end of an 85-day trial of flexible-dose topiramate (50–300 mg/day) [107]. …”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%